Lifestyle interventions and risk of Type 2 diabetes - Bazhan, Marjan; Mirmiran, Parvin; Mirghotbi, Mostafa; Vafaee, Reza (Archives of Advances in Biosciences, 2013)
Diabetes mellitus is one of the most common chronic diseases in nearly all countries. It is difficult to treat and expensive to manage. The development of type 2 diabetes is strongly related to lifestyle factors, thus it might be a preventable disease. Observational studies and intervention trials have shown that physical activity, weight loss and dietary intake including whole grain, dietary fiber and dietary fat are important in delaying and preventing type 2 diabetes. The aim of this review is to gather current information from epidemiologic and clinical trial studies on dietary and lifestyle practices for reducing the risk of type 2 diabetes. The review focuses on the macro and micronutrients, food items and dietary patterns which have been identified as significant in the prevention and management of type 2 diabetes. Also, the role of physical activity and weight loss are presented.